2007
DOI: 10.1016/j.jet.2006.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Imitation—theory and experimental evidence

Abstract: We introduce a generalized theoretical approach to study imitation and subject it to rigorous experimental testing. In our theoretical analysis we find that the different predictions of previous imitation models are due to different informational assumptions, not to different behavioral rules. It is more important whom one imitates rather than how. In a laboratory experiment we test the different theories by systematically varying information conditions. We find significant effects of seemingly innocent change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
170
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 24 publications
14
170
3
2
Order By: Relevance
“…Apesteguía, Huck, and Oechssler (2007) show that PCW is also the unique stochastically stable outcome for a wide range of other imitation rules, including Schlag's (1998) proportional imitation rule, and the imitate-the-best-average rule of Eshel, Samuelson, and Shaked (1998). Alós-Ferrer and Ania (2005) show that stochastic stability of the PCW outcome follows also from the fact that it is a strict nite-population ESS in the sense of Scha er (1988).…”
Section: Dynamic Adjustment Modelsmentioning
confidence: 93%
See 1 more Smart Citation
“…Apesteguía, Huck, and Oechssler (2007) show that PCW is also the unique stochastically stable outcome for a wide range of other imitation rules, including Schlag's (1998) proportional imitation rule, and the imitate-the-best-average rule of Eshel, Samuelson, and Shaked (1998). Alós-Ferrer and Ania (2005) show that stochastic stability of the PCW outcome follows also from the fact that it is a strict nite-population ESS in the sense of Scha er (1988).…”
Section: Dynamic Adjustment Modelsmentioning
confidence: 93%
“…Nevertheless, the heuristic has been quite descriptive of laboratory behavior reported by several authors in low-information environments where players observe other players' quantity choices and pro ts but not the underlying payo function. Most of these studies feature what has been considered long horizon repeated interaction of around 50 periods (see, for example, Huck, Normann, and Oechssler 1999, O erman, Potters, and Sonnemans 2002, or Apesteguía, Huck, and Oechssler 2007.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one experiment (Hampton, Bossaerts, & O'Doherty, 2008) used computational modeling to provide insight into the process of mentalizing about another player's strategy in a game known as the Inspection Game. Additionally, Apesteguia, Huck, and Oechssler (2007) demonstrated that when given the opportunity to view other player's behavior in a game, people will often imitate the strategy that provides the highest payoff. Greater discrepancies between an individual's payoff and another player's payoff result in an increased likelihood of switching to the other strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Vega-Redondo, 1997, Apesteguia et al 2006, Schipper, 2004. The rule "imitate the best" simply requires to choose the best action that was observed in the previous period.…”
Section: Imitate the Best (Imi)mentioning
confidence: 99%
“…In that case both competitors have very low profits or even suffer losses. 2 There is already a small literature on experiments where subjects play against computers. Most of this literature is concerned either with mixedstrategy equilibrium in zero-sum games or with controlling for social preferences or fairness considerations.…”
Section: Introductionmentioning
confidence: 99%